Desrargas epileptiformes intercríticasy la representación cortical del lenguaje en niños con epilepsia de rolando, aportes de la neuropsicología y el SPECT cerebral. - Andrade Machado, René; de la Cruz Turruelles, Alexander; García Espinosa, Arlety; Machado Rojas, Arlán; Herrera Jiménez, Luis Felipe; Arteché Prior, Marianela (Revista Mexicana de Neurociencia)
Introduction: Benign Childhood Epilepsy with centro-temporal spikes is an idiopathic partial epileptic syndrome accepted by ILAE since 1989. Cognitive impairment may be observed in large series of patients with this syndrome. The effect of spikes localization on cerebral organization of language function either contribution of functional images techniques had not been study entirely in order to understand this syndrome. Objective: To determine if spike s localization could modified cortical language organization depending of the time with seizures and whether interictal SPECT images show hypoperfusion areas related with cortical language areas. Patients and method: Right-handle children were assigned in to three age and sex mates group: the first account for healthy child, second group was divided in two other group depending of localization of spikes, one with left cortical spikes and the other with right cortical spikes. We assessed the functional reorganization of cortical language areas employed cognitive paradigm described by Cook and Kinsbourne. Cerebral blood flow was assessed in children with seizures, cognitive deficits and left cortical spikes. Result: The study included a total of 25 children with seizures and 236 healthy children. Forty of 25 children had spikes located in the right cortical hemisphere, the other 11 had spikes on the left cortical side. Functional language reorganization was found after 10 month of seizures onset. We reported cortical hipoperfused areas related with epileptic focus's side (p = 0.01). Conclusion: Inhibition on epileptic focus's side is associated with a bihemispheric cortical language representation. These features seem to be related with the time of seizures onset.